KUALITAS DAN MANFAAT MODEL PENERJEMAHAN TEKS TRANSAKSI JASA VALUTA ASING Dl PT. BANK NEGARA INDONESIA (PERSERO) TBK BANK CIC BANK Bll DAN PT. BANK MANDIRI (PERSERO) TBK SURAKARTA - Sri Purwanti Hery, Ipung (-)
This research was a discriptive qualitative study, which analysis a social process in texts translation model of Foreign Services transactions within a number of banks in Surakarta. The analysis was based on Systemic Functional Linguistics Approach and National Banking Policy. In this research, the researcher studied the quality and benefit of texts translation model of Foreign Services transactions and the Principles of Translation as well as the National Banking Policy based on the register, cohesion system and text structures point of view. The objectives of this research were to find out the translation quality and benefit of the Foreign Secvices transactions texts by discribing : (1) the translation quality of Foreign Services transactions texts ; (2) the translation benefit of Foreign Services texts ; (3) The register of those Foreign Services transactions texts written in two languages i.e. English — Indonesian viewed from the lexicogramatical system, cohesion system and their texts structures ; (4) to know the banker's acquisition in understanding the Foreign Services texts ; (5) to know the customer's acquisition in understanding texts in relation to the required services of transfer, collection, exchange dealing and application of L/C services in PT. Bank Negara Indonesia (Persero) Tbk, Bank CIC, Bank BH and PT. Bank Mandiri (Persero) Tbk Surakarta. The data of this research were lexicogramatical systems, cohesion system and text structure of Foreign Services transaction texts covering transfer, collection, exchange dealing and application of L/C, In this research, the researcher applied purposive sampling. From a number of general bank in Surakarta the researcher considered four of them, two state banks and two private banks. Since the purpose of this research was to see the texts translation model quality and benefit, so the purposive sampling was carried out by selecting samples based on certain criteria. After doing the selection based on the criteria, the researcher chosed PT. Bank Negara Indonesia (Persero) Tbk, Bank CIC, Bank BO and PT. Bank Mandiri (Persero) Tbk Surakarta, for each bank giving services of foreign services by using the transactions tools of texts written in two languages i.e. English and Indonesian. The data in this research, i.e. the texts of Foreign Services transactions in PT. Bank Negara Indonesia (Persero) Tbk, Bank CIC, Bank BE and PT. Bank Mandiri (Persero) Tbk Surakarta were observed and then analyzed by describing the contextual configuration. The data, then, were discribed and interpreted based on lexicogramatical system. To know the quality of the translation, texts of the Foreign Services transactions were analyzed based on field covering the group, lexis, clause system and mood structure, theme/rheme system as well as Transitivity System. At the same time, to know the benefit of the translation, those texts were analyzed based on tenor covering the affect, contact and status as well as mode which covers the aspects of channel and media. Based on the results of data analysis and the discussion after confirming them with the Principles of Translation and the National Banking Policy, the researcher concluded : (1) translation quality of Foreign Services transactions texts in PT. Bank Negara Indonesia (Persero) Tbk, Bank CIC, Bank BE and PT. Bank Mandiri (Persero) Tbk Surakarta is "good enough" ; (2) translation benefit of Foreign Services transactions texts in PT. Bank Negara Indonesia (Persero) Tbk, Bank CIC, Bank BE and PT. Bank Mandiri (Persero) Tbk Surakarta is "quite useful".